2013
DOI: 10.1021/la402263w
|View full text |Cite
|
Sign up to set email alerts
|

Surface Occupancy Plays a Major Role in Cholesterol’s Condensing Effect

Abstract: The condensing power of cholesterol and 5α-cholestane has been examined in liposomal membranes made from 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC). Quantitative nearest-neighbor recognition (NNR) analysis and fluorescence measurements using phase-sensitive probe Laurdan have demonstrated that 5α-cholestane exhibits a substantially weaker condensing effect. This fact, in and of itself, provides compelling evidence that cholesterol's condensing effect is critically dependent on having its steroid nucleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Cholesterol is a flat molecule maximizing the hydrophobic forces in model phospholipid membranes . Cholesterol hereby acts as a fluidity buffer, and this leveling effect leads to a liquid-ordered membrane phase .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol is a flat molecule maximizing the hydrophobic forces in model phospholipid membranes . Cholesterol hereby acts as a fluidity buffer, and this leveling effect leads to a liquid-ordered membrane phase .…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol is a flat molecule maximizing the hydrophobic forces in model phospholipid membranes. 1 Cholesterol hereby acts as a fluidity buffer, 2 and this leveling effect leads to a liquidordered membrane phase. 3 In a nonideal mixture of low-and high-melting glycerophospholipids, cholesterol associates preferentially with the high-melting, saturated lipids.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chol has a pronounced effect on the thermotropic phase behavior and organization of DPPC bilayers ( 23 , 24 ). The high stability of DPPC liposomes containing Chol has been demonstrated and explained by the formation of stronger condensed binary complexes in these lipid layers ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…6. The cholesterol is seemed to incorporate in a lipid bilayer membrane such as liposome, remove the membrane interdigitation, and induce a liquid-ordered phase [27,28]. It is suggested that a high amount of cholesterol orientates in the acyl chain of the C 12 -GLG-C 12 membrane more than liposomes due to the spacer of C 12 -GLG-C 12 consisting two glutamic acids and a lysine is larger than that of phosphatidylcholine.…”
Section: Discussionmentioning
confidence: 99%